Proposal of a specific test in tennis: Test of shot speed and precision - Alfonso-Asencio, M.; Hellín-Martínez, M.; Sánchez-Alcaraz, B. J. (Coaching and Sport Science Review, 2020)
Tennis is a sport in which various variables related to performance influence the final result of a match. The speed and precision of the shots are among the most decisive of them. The objective of this study was to develop a test to assess the performance in terms of the speed and the precision of the forehand, backhand and serve of tennis players. The sample consisted of 4 amateur players. The analysis of the data obtained in the test provides the coach with information about the level of performance of the players and their progression